(untitled) (Research, Society and Development, 2022)
According to the Brazilian Institute of Geography and Statistics (IBGE), in 2019 there were 32 million people over 60 years old in Brazil, and it is expected that in 2060 this number will grow to 58 million elderly people, being, 25% of the Brazilian population. This article presents an analysis of a simulated Long Stay Institution for the Elderly (ILPI) based on innovative approaches, where the focus is the use of gelotology (scientific study of humor and laughter) and integrative practices in all thought and care practice. . The use of these methods, although studied over the years, is still little guided by their effects on the body of the institutionalized elderly, even though it is a current need. In this way, several literatures and specific articles about the use of iceology in the elderly, integrative practices, and civil engineering were qualitatively evaluated, focusing on the use of sustainability and positive architecture, establishing and increasing health promotion, quality of life and well-being of this part of the population, the networks of services and health systems, as well as the optimization of scientific production with a theoretical basis.